Implementation of the Distribution of Welfare Rice Social Assistance for the Poor Southeast Minahasa - Tangel, Nathalia; Mamonto, Fitri; Kandouw, Selpius R. (Technium Social Sciences Journal, 2021)
Poverty is still one of the issues that continue to grow. Efforts to create a prosperous society are strongly influenced by poverty in the region because of the relatively high poverty level. The government has launched a Non-Cash Food assistance program that beneficiaries can use. This article aims to investigate the implementation of assistance from the government to the community. Investigate the implementation of the aid from the aspect of socialisation, effectiveness and suitability of targets. The method used in this research is qualitative. Qualitative research is descriptive, the data collected is in the form of words or pictures, so it does not emphasise numbers. Data collection techniques using in-depth interviews, observation, and documentation. Qualitative data analysis (Miles and Huberman) with procedures, data reduction, data presentation, drawing conclusions or verification. The results showed that social welfare rice assistance for beneficiaries in Ratatotok District, Southeast Minahasa Regency. It had been running according to the applicable rules, following the procedures set by the government. The acceptance of people receiving social assistance prosperous Rice into the excellent category, participate in socialisation activities, participate in the provision of the necessary administrative requirements, and support the officers in disseminating information to other residents and the required cooperation attitude between citizens.